Un carteggio di fine secolo - Claudia, Lazzeri (Firenze University Press, 2006)
The correspondence between Renato Fucini and Emilia Peruzzi, which embraces a period of time comprised between 1871 and 1899, provides a colourful picture of late nineteenth-century Florentine and Italian society. Parading before our eyes are leading figures from Italian political and literary circles, such as Sonnino, Pareto, De Amicis and Ada Negri, who were part of the prestigious entourage that gravitated around the Peruzzi salon. The letters contained in the book throw new light on the personality of Fucini, while at the same time elucidating the biographical details of his life which are still little known and studied.